Outrunning protein diffusion to the air–water interface in cryoEM - Anastasiia Gusach; Kasim Sader; Christopher J. Russo (Proceedings of the National Academy of Sciences, 2025)
Here, we report a series of measurements indicating that it is physically possible to thin and vitrify a specimen for electron cryomicroscopy (cryoEM) faster than proteins diffuse to the air–water interface. We achieved this by spraying picoliter volume droplets at speeds of hundreds of meters per second into a thin layer of liquid ethane coating the surface of a precooled specimen support. The droplets simultaneously collapsed and froze in microseconds into the amorphous phase as they landed on the surface. The atomic structure of the proteins was preserved and tomographic reconstructions of the vitrified specimens indicated adhesion to the interfaces was eliminated. Improved control of the final thickness of the specimen and the orientation distribution of the particles are now the limiting factors. This demonstration provides a basis for the development of specimen preparation methods and instruments that eliminate the detrimental effects of the air–water interface in cryoEM.